Agency and Institutions in Organization Studies. Issue 12 (December 2017) - Abdelnour, Samer; Hasselbladh, Hans; Kallinikos, Jannis
Agency and institutions are essential concepts within institutional theory. In this Perspectives issue, we draw on a select group of Organization Studie s articles to provide an overview of the topic of agency and institutions. We first consider different ways of defining agency and institutions and examine their implications for institutional theory. We then analyse the relationship of actors and institutions through four lenses – the wilful actor, collective intentionality, patchwork institutions and modular individuals . Our analysis leads us to dissociate agency from individuals and view it as a capacity or quality that stems from resources, rights and obligations tied to the roles and social positions actors occupy. Roles and social positions are institutionally engineered. It is social actors qua occupants of roles and positions (not individuals) that enter the social 'stage' and exercise agency.